2017
DOI: 10.1038/s41598-017-08530-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of One-Week Empirical Antibiotic Therapy on the Early Development of Gut Microbiota and Metabolites in Preterm Infants

Abstract: The early postnatal period is the most dynamic and vulnerable stage in the assembly of intestinal microbiota. Antibiotics are commonly prescribed to newborn preterm babies and are frequently used for a prolonged duration in China. We hypothesized that the prolonged antibiotic therapy would affect the early development of intestinal microbiota and their metabolites. To test this hypothesis, we analyzed the stool microbiota and metabolites in 36 preterm babies with or without antibiotic treatment. These babies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 40 publications
5
31
0
Order By: Relevance
“…From the 434 screened studies related to this topic, 15 potentially eligible articles met the pre-established inclusion criteria, including the use of 16S rRNA gene sequencing methodology to analyze biological samples ( Table 1). All studies reported on the antibiotic-induced impact on the composition of neonatal gut microbiota, but treatment options differed between studies: seven studies had mothers receiving intrapartum antibiotics (IPA) [12,[60][61][62][63][64][65] five studies focused on postnatal antibiotic therapy [10,[66][67][68][69]. A further two studies assessed pre and postnatal antibiotic therapy: Zou et al analyzed the effects of prenatal antibiotic exposure and the intensity of prenatal and postnatal antibiotic exposure on gut microbiota of preterm infants [70].…”
Section: Gut Dysbiosis Induced By Antibiotic and Nonantibiotic Medicamentioning
confidence: 99%
See 4 more Smart Citations
“…From the 434 screened studies related to this topic, 15 potentially eligible articles met the pre-established inclusion criteria, including the use of 16S rRNA gene sequencing methodology to analyze biological samples ( Table 1). All studies reported on the antibiotic-induced impact on the composition of neonatal gut microbiota, but treatment options differed between studies: seven studies had mothers receiving intrapartum antibiotics (IPA) [12,[60][61][62][63][64][65] five studies focused on postnatal antibiotic therapy [10,[66][67][68][69]. A further two studies assessed pre and postnatal antibiotic therapy: Zou et al analyzed the effects of prenatal antibiotic exposure and the intensity of prenatal and postnatal antibiotic exposure on gut microbiota of preterm infants [70].…”
Section: Gut Dysbiosis Induced By Antibiotic and Nonantibiotic Medicamentioning
confidence: 99%
“…Arboleya et al evaluated the effects of IPA and postnatal antibiotics administered in the first week versus the second week of life [72]. Six studies reported a decrease in microbial diversity induced by antibiotics [10,62,[64][65][66]71], while three studies showed no statistically significant differences between the antibiotic exposure and antibiotic-free groups [67,69,70]. Low microbial diversity indices were associated with NEC and a high risk of obesity and inflammatory diseases [73].…”
Section: Gut Dysbiosis Induced By Antibiotic and Nonantibiotic Medicamentioning
confidence: 99%
See 3 more Smart Citations